Mencermati Gagasan Islamisasi Ilmu Faruqi - Soleh, Achmad Khudori (el Harakah: Jurnal Budaya Islam, 2002)
Due to the secular paradigm, modern (Western) knowledge becomes dry, even apart from the monotheistic or theological values. Consequently, modern science sees nature and man as mere material and incidental existence without God's interference, so that it can be exploited without calculation. This paper reviews the idea of Faruqi bringing together the secular and Western paradigm in the birth of modern monotheistic scholarship. The Islamization program of Faruqi science emphasizes on the total overhaul of western social science because it is considered Eurocentric. The steps of Islamization of the given science and its criticism of the reality of Islamic education is a major contribution to the reform of the Islamic education system. The ideas that need to be conveyed are first, the relevance of Islam in every field of science. Second, the principle of the unity of truth and knowledge. Thirdly, objective criteria in providing an epistemological basis for the natural and social sciences today are mistaken. Fourth, the discipline of science is not regulated and appears immediately. Akibat paradigma yang sekuler, pengetahuan modern (Barat) menjadi kering, bahkan terpisah dari nilai-nilai tauhid atau teologis. Akibatnya, sains modern melihat alam dan manusia hanya sebagai material dan insidental yang eksis tanpa interfensi Tuhan, sehingga ia bisa dieksploitir tanpa perhitungan. Tulisan ini mengulas gagasan Faruqi mempertemukan paradigma sekuler dan Barat dalam melahirkan keilmuan modern yang bertauhid. Program Islamisasi ilmu Faruqi menekankan perombakan total atas keilmuan sosial barat karena dianggap bersifat Eurosentris. Langkah-langkah Islamisasi ilmu yang diberikan dan kritiknya terhadap realitas pendidikan Islam merupakan sumbangan besar bagi perombakan sistem pendidikan Islam. Gagasan yang perlu di sampaikan adalah pertama, relevansi Islam di setiap bidang ilmu pengetahuan. Kedua, prinsip kesatuan kebenaran dan pengetahuan. Ketiga, kriteria objektif dalam memberikan basis epistemologi bagi ilmu alam dan sosial saat ini dirasa keliru. Keempat, disiplin ilmu tidak diatur dan muncul serta merta.